A unidade corpo-alma na fisiologia-ética do Timeu de Platão - Karina Lucia Fabrini de Morais (2009)
This study is an attempt to carry out an inquiry on the statute of the body and soul relationship within the scope of Phaedo and Timaeus while supporting the thesis of the unity of the body and soul as an expression of Plato¡¦s anthropological thought in these Dialogues. This work shows that such a relationship cannot be elucidated by means of a radical affirmation of the impossibility of an articulation between body and soul, although some passages, especially in Phaedo, rouse an ambiguity due to Plato¡¦s approach of the issue. Thus, we sustain that in this very Dialogue the Philosopher would have supported the thesis of the unity of the body and soul, by taking into account the presence of the dramatic elements and the language used by Plato to describe the nature of the relationship. In our understanding of Timaeus, we explore its conception of human nature as a ãåÞÑÝÖ¥äÕâßÞ, a concept expressing the structural unity of the ¡§body and soul compound¡¨, which is Man. The way Plato approaches the issue in this Dialogue shows that the body can only be considered within its relationship with the soul. In this sense, this study discusses the theses of the generation and corruption of the ¡§body and soul compound¡¨, and that of the statute of the marrow and the location of the soul in Man. The notion of àTáßÚ/affection is a key point in the understanding of the body and soul relationship, inasmuch as it forms the very ground on which to understand the various modalities of such relationship. By means of which we can understand that, in the last instance, every affection must be attributed to the body and soul entirety/wholeness.